Prognostic value of normal stress myocardial perfusion imaging and ventricular function in Japanese patients with chronic kidney disease: a study based on the J-ACCESS-3 database. - Matsuo, Shinro; Nakajima, Kenichi; Takeishi, Yasuchika; Nishimura, Tsunehiko (European Journal of Nuclear Medicine & Molecular Imaging, 2018)
Background: The purpose of this study is to test the hypothesis that a normal myocardial perfusion imaging (MPI) study in chronic kidney disease (CKD) can provide benign prognostic information for the prediction of major cardiovascular events.Methods: The study group consisted of 431 CKD patients (males, 64%; mean age, 72 ± 11 years) with normal SPECT imaging. Based on SPECT image and QGS data, 331 had a summed stress score of 3 or less, a summed difference score of 1 or less and normal cardiac function (males; end-systolic volume (ESV) ≤ 60 ml, females; ESV ≤ 40 ml, males, ejection fraction (EF) ≥ 49%; females, EF ≥ 50%).Results: During a 3-year follow-up period, there were a total of 27 major cardiovascular events, including cardiac death (n = 3), sudden death (n = 3), and acute coronary syndrome (n = 3), and 19 were hospitalized because of congestive heart failure. Kaplan-Meier analysis showed that the number of major cardiovascular events in patients with higher eGFR of ≥ 15 ml/min) were very few, and regarded as low risk. According to the eGFR status, namely < 15 (n = 58), 15 to < 30 (n = 97), 30 to < 45 (n = 131), ≥ 45 (n = 45), the higher cardiac event rate was observed in patients with eGFR of < 15 ml/min among the four groups. The major cardiovascular event rate in patients with the lowest eGFR (< 15) was twice as much than that in patients with eGFR of ≥ 30 ml/min. Lower hemoglobin (males, < 12 g/dl; females, < 11 g/dl) and higher CRP (CPR ≥ 0.3 mg/dl) were also the predictors of increased risk.Conclusions: Normal stress SPECT images confer a benign prognosis in patients with CKD, but care must be taken for severely reduced renal function, which was associated with higher cardiac event.